Polyacrylonitrile/magnesium oxide-based activated carbon nanofibers with well-developed microporous structure and their adsorption performance for methane - Che Othman, F.E. (Korean Society of Industrial Engineering Chemistry, 2017)
PAN-based ACNFs incorporated with MgO was prepared by electrospinning process followed by appropriate activation process. The addition of MgO caused physicochemical changes in term of smaller fiber diameter with an average diameter of 520 nm and higher surface area which is up to four times (1893 m2 g−1) as compared to pristine ACNFs (478 m2 g−1). Moreover, the modified ACNFs possessed a better adsorption capacity with higher CH4 adsorption of 2.37 mmol g−1. From the experimental data, the adsorption of CH4 by composite ACNFs obeyed the pseudo-second order kinetic model with R2 value up to 0.9996 and best fitted by Freundlich isotherm model. © 2017 The Korean Society of Industrial and Engineering Chemistry